2016
DOI: 10.1038/srep25484
|View full text |Cite
|
Sign up to set email alerts
|

A novel quasi-solid state electrolyte with highly effective polysulfide diffusion inhibition for lithium-sulfur batteries

Abstract: Polymer solid state electrolytes are actively sought for their potential application in energy storage devices, particularly lithium metal rechargeable batteries. Herein, we report a polymer with high concentration salts as a quasi-solid state electrolyte used for lithium-sulfur cells, which shows an ionic conductivity of 1.6 mS cm−1 at room temperature. The cycling performance of Li-S battery with this electrolyte shows a long cycle life (300 cycles) and high coulombic efficiency (>98%), without any consuming… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 37 publications
3
33
0
Order By: Relevance
“…6B ) attributed to massive solvent oxidation and decomposition. Theoretically, the instability of liquid-phase DOL/DME to a large extent originates from the DOL with an unstable cyclic structure ( 38 , 39 ), which implies that, after a ring-opening polymerization process where the cyclic DOL is, in advance, stabilized in the long-chain linear structure, the tolerance of electrolyte toward electrochemical progress under high voltage could be improved. As proof, the linear sweep voltammetry (LSV) curve presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…6B ) attributed to massive solvent oxidation and decomposition. Theoretically, the instability of liquid-phase DOL/DME to a large extent originates from the DOL with an unstable cyclic structure ( 38 , 39 ), which implies that, after a ring-opening polymerization process where the cyclic DOL is, in advance, stabilized in the long-chain linear structure, the tolerance of electrolyte toward electrochemical progress under high voltage could be improved. As proof, the linear sweep voltammetry (LSV) curve presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…3,40,65 Furthermore, several studies in the field of Li/S battery research demonstrated that polysulfides can be dissolved in PEO, showing high mobility in Li/S cells with SPEs. [66][67][68] It can therefore be assumed that removal of the LSPS decomposition products, i.e., of Li-ions and polysulfides, into the polymer is a driving force for the oxidation of LSPS, following the principle of Le Chatelier.…”
Section: Discussionmentioning
confidence: 99%
“…The LE (DOL/DME) started to become unstable at 4.00 V and showed a serious decomposition at about 4.20 V [23] . The instability of LE largely originates from the relatively unstable cyclic structure of DOL [24] . In the case of GEL, the onset potential for the decomposition was found to be higher than 4.00 V pointing to the encapsulation of electrolyte within the GEL structure.…”
Section: Resultsmentioning
confidence: 95%